Behavioural Patterns in Captive Common Buzzards Buteo Buteo (Global Journal of Medical Research, 2015)
Captive common buzzards develop adaptive behaviors for survival or vices in response to the stress of captivity, reduced living space, regular handling and change in diet and environment. The studied buzzards showed behaviors suggestive of hierarchy, domination and subservience. Strong and dominant birds would walk briskly across the rooms, stepping on others without challenge or resistance. The weak birds lie prostrate and motionless on the floor anytime the dominant bird spurs up aggressively. This investigation sort to find the purpose mews serve buzzards in captivity; the factors that influence them and the number of mews per minute in different circumstances. They were studied in groups in different rooms to find the mew rate with the observer out of sight, in sight and waving hand. Increase in buzzard population did not increase the mew rate significantly with the observer in sight. The observer coming to sight or otherwise produced a disproportionate increase and decrease in mew rate as the population increased. The study shows that mews by captive buzzards are means of communication and signals and their pitch and frequency were positively influenced by sight and movement. The non-parametric methods (sign test) of comparing mew rates with observer waving hand and not waving hand shows that; z-value=2.04 p=0.041 wilcoxon matched paired test z-value=2.04 p=0.028 Both analysis show significant differences as waving of hand triggered off an exaggerated response as it indicates imminent danger attack or disturbance. Buzzards mew in sympathy to themselves and the high-pitched mews may be their defense against apparent treats, invasion or response to movement. The pitches of the mews were higher with the observer in sight and the observer waving hand. The figures recorded with the observer out of sight,in sight and waving hand suggested that there must be a neuro-endocrinal or nervous/humoral interplay which accounts for the exaggerated responses in terms of pitch
Keywords: behavioural; patterns; captive; common buzzards